Joint Associations of Obesity and NT‐proBNP With the Incidence of Atrial Fibrillation in the ARIC Study - Almuwaqqat, Zakaria (J Am Heart Assoc, 2019)
BACKGROUND: Circulating NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) levels, a well‐known indicator of atrial wall stress and remodeling, inversely correlate with body mass index. Both are strongly predictive of atrial fibrillation (AF). Their potential interaction in relation to incident AF, however, has not been explored. METHODS AND RESULTS: In total, 9556 participants of the ARIC (Atherosclerosis Risk in Communities) study who had 2 measurements of NT‐proBNP and no baseline AF or heart failure were followed from 1996 to 1998 through 2016 for the occurrence of incident AF. Participants were categorized as obese (body mass index ≥30) and nonobese (body mass index <30) and by NT‐proBNP levels (using the median of 68.2 pg/mL as the cutoff). Over a median follow‐up of 18.3 years, we identified 1806 incident cases of AF. Analysis using multivariable Cox regression models showed that obese participants with high NT‐proBNP levels at visit 4 had a higher adjusted risk of incident AF (hazard ratio: 3.64; 95% CI, 3.15–4.22) compared with nonobese individuals with low NT‐proBNP levels. The association of obesity with AF risk was not modified by NT‐proBNP levels (P=0.46 for interaction). Increasing BNP among participants from 1990–1992 to 1996–1998 was associated with increased AF risk. After further adjustment for clinical risk factors and medications, results were similar. CONCLUSIONS: Individuals who had both elevated body mass index and NT‐proBNP and were free of clinically recognized heart failure were at higher risk of AF development. Those who experienced an increase in NT‐proBNP levels between visits 2 and 4 were at higher risk of AF.